What does it Mean to be Blind - Spilsbury, Louise (UK Heinemann, 2002)
This is one of a series designed to present the facts and promote awareness and understanding of conditions that many children learn to live with. It covers the help and support available and includes real-life case studies.
Include Clolor Illustrations, Glossary and Index
Keywords: Blindness -- Every Day Challenges